Biosecurity implications of exotic beetles attacking trees and shrubs in New Zealand - Brockerhoff, E.G.; Bain, J. (New Zealand Plant Protection, 2000)
A survey of exotic beetles that attack trees or shrubs in New Zealand found 51 species of mainly Australian (58) and European (25) origin In addition three biological control agents have been released against woody adventive plant pests The host range of most species is restricted to exotic crop and ornamental plants in New Zealand Nine polyphagous borers sometimes attack dead wood of indigenous species and at least one polyphagous root feeder may attack indigenous trees but the ecological impact of these species on indigenous forests appears negligible However some of the wood and bark borers as well as several defoliators are important pests of exotic crop and amenity plants Although this suggests that exotic phytophagous beetles pose a greater biosecurity threat to exotics than to indigenous species a greater surveillance effort in New Zealands indigenous forests appears necessary to detect potentially harmful invasions